2023
DOI: 10.1038/s41591-023-02211-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association analysis of 77,539 genomes reveals rare disease etiologies

Abstract: The genetic etiologies of more than half of rare diseases remain unknown. Standardized genome sequencing and phenotyping of large patient cohorts provide an opportunity for discovering the unknown etiologies, but this depends on efficient and powerful analytical methods. We built a compact database, the ‘Rareservoir’, containing the rare variant genotypes and phenotypes of 77,539 participants sequenced by the 100,000 Genomes Project. We then used the Bayesian genetic association method BeviMed to infer associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…This result is consistent with the pattern observed in the previous study (Domazet-Lošo and Tautz 2008). By utilizing DNVs and rare variants from large-scale datasets of exomic and genomic sequencing aggregated in recent years (Wang et al 2022;Greene et al 2023), we found that evolutionary older genes tend to have higher gene-wise DNVs burden. Logistic regression modeling indicates that protein length, gene age, and DNVs burden are positively correlated with the probability of genes as being disease genes.…”
Section: The Roles Of Young Genes In Human Biomedically Important Phe...supporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with the pattern observed in the previous study (Domazet-Lošo and Tautz 2008). By utilizing DNVs and rare variants from large-scale datasets of exomic and genomic sequencing aggregated in recent years (Wang et al 2022;Greene et al 2023), we found that evolutionary older genes tend to have higher gene-wise DNVs burden. Logistic regression modeling indicates that protein length, gene age, and DNVs burden are positively correlated with the probability of genes as being disease genes.…”
Section: The Roles Of Young Genes In Human Biomedically Important Phe...supporting
confidence: 91%
“…We retrieved the burden of de novo germline variants from multiple studies, including the Gene4Denovo database (68,404 individuals) (Zhao et al 2020), UK Biobank exomes (394,783 individuals), and gnomAD database (V4.0, 76,215 individuals) (Wang et al 2022;Greene et al 2023). The genotypes and allele frequencies were downloaded from gno-mAD (https://gnomad.broadinstitute.org/downloads).…”
Section: Logistic Regression Modeling and Model Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…While both GPR156 (Greene et al, 2023; Ramzan et al, 2023) and GPSM2 (Doherty et al, 2012; Walsh et al, 2010) have been identified as human deafness genes, there is currently no evidence implicating a GNAI/O protein. This is most likely because all GNAI/O proteins, including GNAI3 which is more specifically required in HC for hair bundle morphogenesis (Figure 9), play ubiquitous and critical signaling roles in the context of heterotrimeric protein signaling across many cell types.…”
Section: Discussionmentioning
confidence: 99%
“…These are not rare occurrences: recently, a research group described matching immediately upon submission to MME to an existing cohort with phenotypic and genetic similarities for almost ~10% of their novel candidate genes 51 Finally, many large-scale clinical and hybrid clinical-research genomic testing efforts are already identifying, sharing, and reporting results in novel candidate genes and have described substantial benefits in identifying a genetic diagnosis for their patients. 28,[31][32][33]51,56 Thus we strongly encourage clinical laboratories and research programs to proactively identify, share, and report variants in novel candidate genes.…”
Section: Rationale For Sharing and Reporting Of Variants In Novel Can...mentioning
confidence: 99%